Habilidades sociales y la prevención del consumo de droga “H” en un estudiante - Jacome Perez, Fatima Nubia (2020)
The present case study addressed a fairly common problem at this time in our educational institutions, in our homes and in general affects all contribute to the tasks of prevention, tertiary as a society intervention is carried out as a whole, the subject The study is a 16-year-old student who uses the drug “h”. It is investigated as the techniques in therapeutic social skills with the purpose of modifying maladaptive behavior patterns. Diagnostic assessment tools such as history were used for this purpose. clinical, analysis of the observation sheet and psychological tests (Millon Test, Ramos Scale) as well as the anxiety state (Beck's anxiety scale) corroborated the presumptive diagnosis of dependence on drug use F11.2 (dependence on heroin) associated with family conflicts Z62.820 (parent-child relationship problem). In order to suppress the consumption of the drug in the adolescent, we proceeded with the planning of a therapeutic scheme based on principles of cognitive behavioral therapy specifically in the training in social skills, obtaining significant positive behavioral changes as well as the suppression of the consumption by the youth In addition to this, improvements in mainly mother-child relationships were the emotional aspect that most affected the maintenance of addictive behaviors.